Girl Reserves rally in San Francisco - Unknown:::Creator::::::::::::
This photograph shows a large group of Girl Reserves posing on the street and in buses in front of the Y.W.C.A. building as they start for a rally in San Francisco. Some of the girls hold a banner with the Girl Reserves emblem on it. A bus driver stands at each end of the picture.